Inhibition of PIKfyve prevents myocardial apoptosis and hypertrophy through activation of SIRT3 in obese mice. Issue 6 (10th April 2017) - Tronchere, Helene; Cinato, Mathieu; Timotin, Andrei; Guitou, Laurie; Villedieu, Camille; Thibault, Helene; Baetz, Delphine; Payrastre, Bernard; Valet, Philippe; Parini, Angelo; Kunduzova, Oksana; Boal, Frederic
Abstract: PIKfyve is an evolutionarily conserved lipid kinase that regulates pleiotropic cellular functions. Here, we identify PIKfyve as a key regulator of cardiometabolic status and mitochondrial integrity in chronic diet‐induced obesity. In vitro, we show that PIKfyve is critical for the control of mitochondrial fragmentation and hypertrophic and apoptotic responses to stress. We also provide evidence that inactivation of PIKfyve by the selective inhibitor STA suppresses excessive mitochondrial ROS production and apoptosis through a SIRT3‐dependent pathway in cardiomyoblasts. In addition, we report that chronic STA treatment improves cardiometabolic profile in a mouse model of cardiomyopathy linked to obesity. We provide evidence that PIKfyve inhibition reverses obesity‐induced cardiac mitochondrial damage and apoptosis by activating SIRT3. Furthermore, treatment of obese mice with STA improves left ventricular function and attenuates cardiac hypertrophy. In contrast, STA is not able to reduce isoproterenol‐induced cardiac hypertrophy in SIRT3.KO mice. Altogether, these results unravel a novel role for PIKfyve in obesity‐associated cardiomyopathy and provide a promising therapeutic strategy to combat cardiometabolic complications in obesity. Synopsis: Obesity is a major risk factor associated with cardiovascular and metabolic diseases. Here, the lipid kinase PIKfyve is shown to be critical for obesity‐mediated phenotypic features. Inhibition of PIKfyve opens new therapeutic avenues to combat cardio‐metabolic complications linked to obesity. PIKfyve is critical for stress‐induced mitochondrial fragmentation. PIKfyve inhibition by STA‐5326 prevents ROS production and apoptosis through SIRT3. Chronic PIKfyve inhibition prevents myocardial damage and cardiac hypertrophy in mice. Abstract : Obesity is a major risk factor associated with cardiovascular and metabolic diseases. Here, the lipid kinase PIKfyve is shown to be critical for obesity‐mediated phenotypic features. Inhibition of PIKfyve opens new therapeutic avenues to combat cardio‐metabolic complications linked to obesity.